Large electro-optic response of bulk ferroelectric crystals enhanced by piezoelectric resonance in the high frequency range. (January 2018) - Li, Jun; Li, Yang; Meng, Qingxin; Zhou, Zhongxiang; Jia, Dechang; McIntosh, Robert; Bhalla, Amar S.; Guo, Ruyan
Graphical abstract: Highlights: The EO effect of ferroelectric Li-doped niobium-rich potassium tantalate niobate single crystals were determined using improved dynamic EO measurement carried out via a continuous frequency scan over the range of frequencies covering the samples' fundamental resonances. Near the piezoelectric resonant peaks, the EO response is enhanced significantly and can be compared with low frequency data, e.g. the effective EO coefficients of the three samples at the resonant peaks are 217.3 pm/V, 155.4 pm/V and 37.6 pm/V, respectively. In KLTN crystals, the lattice vibrations exactly synchronize with the stretching of the dipole at the resonant frequency, and the induced polarizations which exhibit less frequency limitation as compared to photoelasticity. Thus, the enhancement can be attributed to nonlinear polarization and nonzero stress. Abstract: Electro-optic (EO) devices with high EO coefficients at radio and microwave frequencies are integral components of the photonics industry. This work determines the EO effect of ferroelectric Li-doped niobium-rich potassium tantalate niobate (K0.95 Li0.05 Ta1- x Nb x O3 ; KLTN) single crystals using improved dynamic EO measurement. The phase transitions of KLTN crystals were investigated via variable-temperature Raman spectroscopy. A full view of the surface displacement and velocity for the KLTN sample at the resonant frequency was studied using an ultra-frequency vibrometer. The KLTN sample with x = 0.60 exhibits the enhanced effective EO coefficient (γc ) ∼ 217 pm/V near the piezoelectric resonant peaks, which is comparable with the value at low frequency. The piezoelectric enhanced EO property of KLTN single crystals can be attributed to nonlinear polarization and nonzero stress, and showing promising for designing practical optical-piezoelectric-mechanism coupling devices.